QSAR‐driven synthesis of antiproliferative chalcones against SH‐SY5Y cancer cells: Design, biological evaluation, and redesign. Issue 7 (18th April 2022) - Mellado, Marco; Reyna‐Jeldes, Mauricio; Weinstein‐Oppenheimer, Caroline; Covarrubias, Alejandra A.; Aguilar, Luis F.; Coddou, Claudio; Mella, Jaime; Cuellar, Mauricio A.
Abstract: Neuroblastoma is one of the most frequent types of cancer found in infants, and traditional chemotherapy has limited efficacy against this pathology. Thus, the development of new compounds with higher activity and selectivity than traditional drugs is a current challenge in medicinal chemistry research. In this study, we report the synthesis of 21 chalcones with antiproliferative activity and selectivity against the neuroblastoma cell line SH‐SY5Y. Then, we developed three‐dimensional quantitative structure–activity relationship models (comparative molecular field analysis and comparative molecular similarity index analysis) with high‐quality statistical values ( q 2  > 0.7; r 2  > 0.8; r 2 pred  > 0.7), using IC50 and selectivity index (SI) data as dependent variables. With the information derived from these theoretical models, we designed and synthesized 16 new molecules to prove their consistency, finding good antiproliferative activity against SH‐SY5Y cells on these derivatives, with three of them showing higher SI than the referential drugs 5‐fluorouracil and cisplatin, displaying also a proapoptotic effect comparable to these drugs, as proven by measuring their effects on executor caspases 3/7 activity induction, Bcl‐2/Bax messenger RNA levels alteration, and DNA fragmentation promotion. Abstract : After synthesizing 21 chalcones with antiproliferative activity and selectivity against the neuroblastoma cell line SH‐SY5Y, three‐dimensional quantitative structure–activity relationship models were developed with high‐quality statistical values. With the information derived from these theoretical models, 16 new molecules were designed and synthesized to prove their consistency.